2017
DOI: 10.1080/19382014.2017.1405189
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to high dietary advanced glycation end products in transgenic NOD8.3 mice leads to pancreatic beta cell dysfunction

Abstract: The contribution of environmental factors to pancreatic islet damage in type 1 diabetes remains poorly understood. In this study, we crossed mice susceptible to type 1 diabetes, where parental male (CD8+ T cells specific for IGRP206-214; NOD8.3) and female (NOD/ShiLt) mice were randomized to a diet either low or high in AGE content and maintained on this diet throughout pregnancy and lactation. After weaning, NOD8.3+ female offspring were identified and maintained on the same parental feeding regimen for until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…In cell cultures, several food‐derived AGEs were shown to activate inflammatory responses via a RAGE‐dependent pathway (Somoza et al., 2005; Van der Lugt et al., 2018; Zill et al., 2003; Zill, Günther, Erbersdobler, Fölsch, & Faist, 2001). In rodent models, high‐dAGE diets deteriorated pathogenesis mediated by RAGE that are associated with diabetes (Borg et al., 2018; Lin et al., 2003), nephropathies (Yeh, Yang, Pai, Wu, & Chen, 2017), vascular dysfunction (Tikellis et al., 2008), nonalcoholic steatohepatitis (Leung et al., 2016), and Alzheimer's disease (Lubitz et al., 2016). Feeding rats with diets containing bread crust or coffee beverage upregulated the expression level of HMGB1 (ligand of RAGE) in the lungs.…”
Section: In Vivo Metabolism Of Dagesmentioning
confidence: 99%
“…In cell cultures, several food‐derived AGEs were shown to activate inflammatory responses via a RAGE‐dependent pathway (Somoza et al., 2005; Van der Lugt et al., 2018; Zill et al., 2003; Zill, Günther, Erbersdobler, Fölsch, & Faist, 2001). In rodent models, high‐dAGE diets deteriorated pathogenesis mediated by RAGE that are associated with diabetes (Borg et al., 2018; Lin et al., 2003), nephropathies (Yeh, Yang, Pai, Wu, & Chen, 2017), vascular dysfunction (Tikellis et al., 2008), nonalcoholic steatohepatitis (Leung et al., 2016), and Alzheimer's disease (Lubitz et al., 2016). Feeding rats with diets containing bread crust or coffee beverage upregulated the expression level of HMGB1 (ligand of RAGE) in the lungs.…”
Section: In Vivo Metabolism Of Dagesmentioning
confidence: 99%
“…For example, cereal products that are baked at high temperatures contain advanced glycation end products that have been suggested as a risk factor for type 1 diabetes 1314. Grains also contain several other components generally considered harmful to health but that have not yet been studied in relation to type 1 diabetes, such as mycotoxins, heavy metals, and remnants of pesticides and fertilisers 1516…”
mentioning
confidence: 99%
“…There have been previous studies where AGEs have been shown to impair insulin secretion 70,250 although it is unclear as to the role that OST48 plays in beta cells. However, we have identified that OST48 is expressed in beta cells 251 . In addition, further investigation would be required to elucidate why these apparent improvements in insulin secretion seen in diabetic OST48 mice did not translate to improved longterm clinical markers of glycaemic control.…”
Section: Discussionmentioning
confidence: 87%